The Trends of Legal Migration: Reasons of Indonesian Legal Migrants Settling in the Netherlands - Wasisto, Nada Gavrila; Pilongo, Levina Charisa; Satya, Putu Agung Nara Indra Prima (Jurnal Ilmiah Hubungan Internasional, 2023)
Indonesia has been one of the contributing countries in sending migrants to the Netherlands. The historical relations along with the large economic opportunities in the Netherlands play a part in the promotion of cross-border movement for Indonesians to the Netherlands. However, those are only one of many underlying reasons why Indonesians are willing to leave their home country to a more developed country. This article questions the reasons behind Indonesian legal migration in the Netherlands and looks into the trend of Indonesian migrants as the result of the fulfilment of human development embedded in education and employment policies and management in the Netherlands. The relationship between the two aspects and the Indonesian migration in the Netherlands is examined through the Theory of Human Development by Amartya Sen, specifically in regard to the improvement of human capabilities and freedom of choice. The authors found that a country that promotes human development is more favourable to live in. Thus, in this case, the education and employment policies and mechanisms of the Netherlands that are focusing on the fulfilment of freedom of choice and the improvement of human capabilities attract international migrants, particularly the Indonesians.   Keywords: the Netherlands; Indonesia; Legal Migrants; Migration